The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1108/intr-11-2013-0232
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationships of critical factors to Facebook educational usage intention

Abstract: Purpose -The purpose of this paper is to conceptualise a framework that integrates information quality, system quality, function quality, and social influence based on the information system (IS) success model, to explore the relationship among these factors, which might be the key determinants of Facebook educational usage intention. Design/methodology/approach -An internet survey was conducted to collect empirical data from 221 Facebook users on their experiences of using Facebook. This study applied structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 59 publications
1
34
0
1
Order By: Relevance
“…The extent to which an individual believes that others expect them to use a new system is referred to as social influence (Venkatesh et al, 2003). Studies carried out have found that social influence has a significant influence on behavioural intention (Hsu & Lin, 2016;Kim & Park, 2011;Ozturk et al, 2016;Wu & Chen, 2015). Davis (1989) believed that subjective norm had no influence on technology acceptance, while Shin (2009) has hypothesized that social influence has a positive effect on the intention to utilize mobile payments, although the effect of social influence on intention was not supported.…”
Section: Social Influencementioning
confidence: 99%
“…The extent to which an individual believes that others expect them to use a new system is referred to as social influence (Venkatesh et al, 2003). Studies carried out have found that social influence has a significant influence on behavioural intention (Hsu & Lin, 2016;Kim & Park, 2011;Ozturk et al, 2016;Wu & Chen, 2015). Davis (1989) believed that subjective norm had no influence on technology acceptance, while Shin (2009) has hypothesized that social influence has a positive effect on the intention to utilize mobile payments, although the effect of social influence on intention was not supported.…”
Section: Social Influencementioning
confidence: 99%
“…Due to the widespread options of connecting online (through smartphone, tablet, computer, etc. ), the Internet has become central in adolescents' lives, as they use it for leisure (e.g., listening to music, watching movies, playing online games), communication (with friends and family), and learning (school tasks, general knowledge; Carlisle et al, 2016 ; Wu and Chen, 2015 ). Several studies have examined the relationships between Internet use and academic performance, indicating positive links between the latter and Internet information seeking among high school students ( Chen et al, 2014 ; Zhu et al, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, plentiful empirical research has assessed the behavior of social media in different environments, such as the educational environment [4,5], knowledge sharing [6], and leisure environment [7,8]. However, members of virtual communities are not just information seeking, but also to seek social interaction and friendship [2].…”
Section: Introductionmentioning
confidence: 99%